The effects of aqueous extract from watermelon (Citrullus lanatus) peel on the growth and physiological characteristics of Dolichospermum flos-aquae - Jin Yan; Peiyao Xu; Fengrui Zhang; Xinyue Huang; Yanmin Cao; Shenghua Zhang (Scientific Reports, 2022)
Abstract Nowadays, the increasing Dolichospermum (Anabaena) blooms pose a major threat to the aquatic environment and public health worldwide. The use of naturally derived chemicals from plants to control cyanobacteria blooms has recently received a tremendous amount of attention. This study investigates the possibility of transforming watermelon peel (WMP) into a biological resource to allelopathically inhibit Dolichospermum flos-aquae blooms. The results demonstrated that the growth of D. flos-aquae was efficiently restricted by the aqueous extract of watermelon peel (WMPAE) in a concentration-dependent manner. Cell viability decreased quickly, intracellular structural damage occurred, chlorophyll a in algal cells degraded, and photosynthesis was clearly inhibited. At the same time, the levels of reactive oxygen species in viable cells increased significantly, as did malondialdehyde levels, indicating that WMPAE elucidated strong oxidative stress and corresponding damage to D. flos-aquae. Capsular polysaccharide (CPS) levels increased in all treatment groups, which represents an adaptive response indicative of the development of resistance to WMPAE stress and oxidative damage. Despite this, WMPAE had clear inhibitory effects on D. flos-aquae. These findings provide fundamental information on an allelopathic system that could be a novel and attractive approach for suppressing D. flos-aquae blooms in small aquatic environments, especially aquaculture ponds.